2021
DOI: 10.3390/w13070921
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Flood Peak Discharge Caused by Overtopping Failure of a Landslide Dam

Abstract: Overtopping failure often occurs in landslide dams, resulting in the formation of strong destructive floods. As an important hydraulic parameter to describe floods, the peak discharge often determines the downstream disaster degree. Based on 67 groups of landslide dam overtopping failure cases all over the world, this paper constructs the calculation model for peak discharge of landslide dam failure. The model considers the influence of dam erodibility, breach shape, dam shape and reservoir capacity on the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…12) for calculating the volume of dam debris. In the case of the Baige landslide dam, the prediction outcome is 32.4×10 6 m 3 , while the true value according to a field survey is 30.2 × 10 6 m 3 (Shen et al, 2020). The error is mainly induced by the elevation change of the riverbed in the direction of the vertical channel, which has a great influence on the area of the dam section when the width of the dam is large.…”
Section: Predicting the Volume Of The Dammentioning
confidence: 96%
See 4 more Smart Citations
“…12) for calculating the volume of dam debris. In the case of the Baige landslide dam, the prediction outcome is 32.4×10 6 m 3 , while the true value according to a field survey is 30.2 × 10 6 m 3 (Shen et al, 2020). The error is mainly induced by the elevation change of the riverbed in the direction of the vertical channel, which has a great influence on the area of the dam section when the width of the dam is large.…”
Section: Predicting the Volume Of The Dammentioning
confidence: 96%
“…Fan analyzed a series of dams induced by the 2008 Wenchuan earthquake and found that 43 % of them collapsed within 1 month (Fan et al, 2012). According to Shen's research on the longevity of barrier lakes, nearly 48.3 % of dams will breach within a week and 84.4 % of dams will fail within 1 year (Shen et al, 2020). Most landslide dams are unstable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations